A Prospective Randomized Multicenter Trial Comparing Clinical Outcomes of Patients Treated Surgically With a Static or Dynamic Implant for Acute Ankle Syndesmosis Rupture. Issue 5 (May 2015) - Laflamme, Mélissa; Belzile, Etienne L.; Bédard, Luc; van den Bekerom, Michel P. J.; Glazebrook, Mark; Pelet, Stéphane
Abstract : Objectives: To compare the clinical and radiographic outcome after stabilization of an acute syndesmosis rupture with either a static implant (a 3.5-mm metallic screw through 4 cortices) or a dynamic device (TightRope; Arthrex). Design: Multicenter randomized double-blind controlled trial. Settings: Study realized in 5 trauma centers (2 level 1 and 3 level 2) in 2 countries. Patients/Participants: Seventy subjects admitted for an acute ankle syndesmosis rupture entered the study and were randomized into 2 groups (dynamic fixation = 34 and static fixation = 36). The 2 groups were similar regarding demographic, social, and surgical data. Sixty-five patients (dynamic = 33 and static = 32) completed the study and were available for analysis. Intervention: Syndesmosis fixation in the static group was realized with a 4 cortices 3.5-mm cortical screw (Synthes) and in the dynamic group with 1 TightRope (Arthrex). Standardized rehabilitation process for the 2 groups: no weight bearing in a cast for 6 weeks and then rehabilitation without protection. Main Outcome Measurement: Olerud–Molander score. Results: Subjects with dynamic fixation achieved better clinical performances as described with the Olerud–Molander scores at 3 (68.8 vs. 60.2, P = 0.067), 6 (84.2 vs. 76.8, P = 0.082), and 12 months (93.3 vs. 87.6, P = 0.046). We also observed higher American Orthopaedic Foot and Ankle Society scores at 3 months (78.6 vs. 70.6, P = 0.016), but these were not significant at 6 (87.1 vs. 83.8, P = 0.26) or 12 months (93.1 vs. 89.9, P = 0.26). Implant failure was higher in the screw group (36.1% vs. 0%, P < 0.05). Loss of reduction was observed in 4 cases in the static screw group (11.1% vs. 0%, P = 0.06). Conclusions: Dynamic fixation of acute ankle syndesmosis rupture with a dynamic device seems to result in better clinical and radiographic outcomes. The implant offers adequate syndesmotic stabilization without failure or loss of reduction, and the reoperation rate is significantly lower than with conventional screw fixation. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.